2015
DOI: 10.1111/cdev.12359
|View full text |Cite
|
Sign up to set email alerts
|

The Caregiving Environment and Developmental Outcomes of Preterm Infants: Diathesis Stress or Differential Susceptibility Effects?

Abstract: The interactions between premature birth and the caregiving environment on infants' cognitive and social functioning were examined. Participants were 150 infants (83 preterm, 67 full-term) and their parents. When infants were 6 months old, parents reported on their levels of emotional distress, and triadic family interactions were filmed and coded. At 12 months of age, the infants' cognitive and social functioning was assessed. Prematurity moderated the effects of maternal (but not paternal) emotional distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 78 publications
11
96
6
1
Order By: Relevance
“…Additionally, in Poehlmann et al’s (2012) study on a group of solely preterm infants, the cognitive outcomes of an easily-distressed subgroup of infants were in line with differential susceptibility. However, in Gueron-Sela et al’s (2015) study – which had a control group of full-term infants – diathesis stress best explained the interaction between prematurity and maternal emotional distress for children born between 28 and 33 weeks. Recent studies of low birth weight infants – who are often, but not exclusively preterm – also found that children’s cognitive and academic outcomes are consistent with diathesis stress (Camerota, Willoughby, Cox, Greenberg, & the Family Life Project Investigators, 2015; Jaekel, Pluess, Belsky, & Wolke, 2015).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Additionally, in Poehlmann et al’s (2012) study on a group of solely preterm infants, the cognitive outcomes of an easily-distressed subgroup of infants were in line with differential susceptibility. However, in Gueron-Sela et al’s (2015) study – which had a control group of full-term infants – diathesis stress best explained the interaction between prematurity and maternal emotional distress for children born between 28 and 33 weeks. Recent studies of low birth weight infants – who are often, but not exclusively preterm – also found that children’s cognitive and academic outcomes are consistent with diathesis stress (Camerota, Willoughby, Cox, Greenberg, & the Family Life Project Investigators, 2015; Jaekel, Pluess, Belsky, & Wolke, 2015).…”
Section: Introductionmentioning
confidence: 87%
“…Gueron-Sela et al’s (2015) study comparing infants born between 28 and 33 weeks gestation and full-term infants showed that preterm infants exposed to higher levels of maternal distress or low quality triadic family interactions demonstrated lower social competence than full-term infants at 12 months of age, while those exposed to low maternal distress or high quality family interactions outperformed the full-term infants on measures of social competence. Because biological risk factors affect social abilities to a smaller degree than cognitive abilities (Bendersky & Lewis, 1994), the social abilities of children born preterm may have more space to be positively impacted by high quality caregiving than their cognitive abilities.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…111,112 Given that children born preterm already have neural and physiological vulnerabilities, they may be even more vulnerable to the deleterious effects of these stressors. 113 Unfortunately, few studies have focused on the joint roles of medical and social risk in shaping executive function outcomes in children born preterm, an important oversight given the potential role of family-based interventions in fostering EF in this population. In one study, young low birth weight children whose parents who were more warm and responsive to the child during structured play activities caught up to NBW controls on measures of EF between ages 3 and 5 years, whereas parents of low birth weight children who were more harsh and intrusive during these interactions remained behind.…”
Section: Effects Of Preterm Birth On Executive Functionmentioning
confidence: 99%